Mast Cells as a Double-Edged Sword in Immunity: Their Function in Health and Disease. First of Two Parts - Magrone, Thea; Magrone, Manrico; Jirillo, Emilio (Endocrine, Metabolic & Immune Disorders-Drug Targets, 2020)
Mast cells (MCs) have recently been re-interpreted in the context of the immune scenario in the sense that their pro-allergic role is no longer exclusive. In fact, MCs even in steady state conditions maintain homeostatic functions, producing mediators and intensively cross-talking with other immune cells. Here, emphasis will be placed on the array of receptors expressed by MCs and the variety of cytokines they produce. Then, the bulk of data discussed will provide readers with a wealth of information on the dual ability of MCs not only to defend but also to offend the host. This double attitude of MCs relies on many variables, such as their subsets, tissues of residency and type of stimuli ranging from microbes to allergens and food antigens. Finally, the relationship between MCs with basophils and eosinophils will be discussed.
Keywords: eosinophils